Silent and silenced disease: a rare presentation of Chagas disease - Gupta, Brajesh B.; Jain, Manali; Bhingare, Pravin; Dakhore, Sanjay; Gupta, Shweta; Bansod, Prasad; Deshmukh, Karishma; Jadhav, Ganesh; Kodape, Amit (International Surgery Journal, 2022)
Chagas disease is an infectious disease caused by the protozoan Trypanosoma cruzi. The disease mainly affects the nervous system, digestive system and heart. The objective of this article is to know about the chronic gastrointestinal manifestations of Chagas which are mainly a result of enteric nervous system impairment caused by T. cruzi infection. The anatomical locations most commonly described to be affected by Chagas disease are salivary glands, esophagus, lower esophageal sphincter, stomach, small intestine, colon, gallbladder and biliary tree. Most people suffer cardiac damage, including cardiomyopathy, heart rhythm abnormalities and often an apical aneurysm.